2000
DOI: 10.1046/j.1365-2044.2000.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet pain in a volunteer study: effect of changes in cuff width and pressure

Abstract: This study examines the relationship between pneumatic tourniquet cuff size, occlusion pressure and the resulting pain. Two tourniquet cuff widths were used, a wide (14 cm) and a narrow cuff (7 cm). Twenty volunteers were divided into two groups for tourniquet application: a pressure group in which the tourniquet was inflated to a pressure equal to the systolic pressure + 100 mmHg, and a saturation group in which the tourniquet was inflated to 10 mmHg above the loss of arterial pulse, as indicated by cessation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 20 publications
4
68
1
6
Order By: Relevance
“…The duration of pain tolerance improves in sedated patients [11,36]. Hagenouw et al (1986) demonstrated that higher cuff pressures with narrower tourniquet diameters can cause less pain than wider cuffs with lower pressures [11], whereas Estebe (2000) showed that a wide-cuff pneumatic tourniquets improve arterial occlusion and are less painful than narrow cuffs when pressure is limited to arterial pulse loss [17,25].…”
Section: Painmentioning
confidence: 99%
“…The duration of pain tolerance improves in sedated patients [11,36]. Hagenouw et al (1986) demonstrated that higher cuff pressures with narrower tourniquet diameters can cause less pain than wider cuffs with lower pressures [11], whereas Estebe (2000) showed that a wide-cuff pneumatic tourniquets improve arterial occlusion and are less painful than narrow cuffs when pressure is limited to arterial pulse loss [17,25].…”
Section: Painmentioning
confidence: 99%
“…Pain thresh old is understood to be a valid indicator of endorphin activity because endogenous opioids are released during pain sensation (DePue & Morrone-Strupinsky, 2005;Mueller, 1981). Specifically, the use of a blood pressure cuff to induce specific ischemic pain has been found to be a valid and reliable, as well as noninvasive, protocol to assess endorphin levels (Estebe, Le Naoures, Chemaly, & Ecoffey, 2000;Ryan & Kovacic, 1966). Cohen, Ejsmond-Frey, Knight, and Dunbar (2010) investigated synchronized behaviors in a team of male collegiate rowers, using the pain threshold test as a noninvasive measure of cen tral endorphin activity.…”
mentioning
confidence: 99%
“…Ne ben der Tour ni quet grö ße, dem In fla tions druck und der Dau er der Tour ni quetan la ge [12,30] als ur säch li che Fak to ren wer den Ad ju van zi en zum Lo kal an äs the tikum wie Clo ni din [14,15] oder Ket amin [15] als schmerz lin dern de Fak to ren dis kutiert. Von meh re ren Au to ren wird al lerdings der lo ka len Haut kom pres si on eine we sent li che Rol le zu ge schrie ben, denn Maß nah men zur ört li chen Be täu bung der Haut durch Li do cain-/Pri lo cain-Sal be oder lo ka le In fil tra tio nen mit Lo kal an äs-the ti ka ver bes sern die Tour ni quet to le ranz [20,24,29].…”
Section: Dis Kus Si Onunclassified